Black Flag, Minor Threat, and the Revival of Traditional Values in American Hardcore Punk - Lee, Sangheon (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2024)
In the aftermath of the economic, political, and social turmoil of the 1960s and early 1970s, American society was dominated, according to Christopher Lasch, by disillusionment, fatigue, and anxiety, leading to an obsession with living in the moment. Moreover, traditional Protestant values such as work ethic, sobriety, self-discipline, and delayed gratification were replaced by the search for instant satisfaction and for pleasure that could be had “right now”—a new, “radical” individualism. American hardcore punk emerged in suburban middle-class residential areas that epitomized the era’s conformity, while its diy ethos was justified and stimulated by this radical individualism, allowing adherents to withdraw from social and political issues and concentrate on their day-to-day personal activities. More interestingly, in their attitude and praxis, hardcore punk micro-entrepreneurs revived a significant part of the older American heritage values, most of which the 1960’s counterculture had scorned.